Improved oral bioavailability and therapeutic efficacy of dabigatran etexilate via Soluplus-TPGS binary mixed micelles system. (3rd April 2017) - Hu, Mei; Zhang, Jinjie; Ding, Rui; Fu, Yao; Gong, Tao; Zhang, Zhirong
Abstract: The clinical use of dabigatran etexilate (DABE) is limited by its poor absorption and relatively low bioavailability. Our study aimed to explore the potential of a mixed micelle system composed of Soluplus ® and D-alpha tocopheryl polyethylene glycol 1000 succinate (TPGS) to improve the oral absorption and bioavailability of DBAE. DBAE was first encapsulated into Soluplus/TPGS mixed micelles by a simple thin film hydration method. The DBAE loaded micelles displayed an average size distribution of around 83.13 nm. The cellular uptake of DBAE loaded micelles in Caco-2 cell monolayer was significantly enhanced by 2–2.6 fold over time as compared with DBAE suspension. Both lipid raft/caveolae and macropinocytosis-mediated the cell uptake of DBAE loaded micelles through P-glycoprotein (P-gp)-independent pathway. Compared with the DBAE suspension, the intestinal absorption of DBAE from DBAE mixed micelles in rats was significantly improved by 8 and 5-fold in ileum at 2 h and 4 h, respectively. Moreover, DBAE mixed micelles were absorbed into systemic circulation via both portal vein and lymphatic pathway. The oral bioavailability of DBAE mixed micelles in rats was 3.37 fold higher than that of DBAE suspension. DBAE mixed micelles exhibited a comparable anti-thrombolytic activity with a thrombosis inhibition rate of 63.18% compared with DBAE suspension in vivo . Thus, our study provides a promising drug delivery system to enhance the oral bioavailability and therapeutic efficacy of DBAE.